Integrated computational and experimental investigation of hybrid mixed-linker ZIF-7-8 crystals for H2/CO2 separation - Yang, Lee; Abdul Razak, Mus’ab; Choong, Thomas Shean Yeaw; Abdul Hamid, Mohamad Rezi (Springer, 2026)
Hybrid mixed-linker ZIF-7-8 crystals were synthesized via the Delayed Linker Addition (DLA) method, enabling controlled incorporation of benzimidazolate (bIm) into ZIF-8 frameworks while retaining the sodalite (SOD) topology. By varying nucleation time (5–17 min) and bIm-to-mIm mass ratio (0.38–1.90), bIm incorporation reached up to 60.8%. The DLA approach also facilitated the integration of non-isostructural linkers, such as imidazole (23.2%) and 2-phenylimidazole (3.1%), expanding framework tunability. Characterization by XRD, FTIR, ¹H-NMR, and N₂ physisorption confirmed gradual pore aperture narrowing, surface area reduction (1,768 to 76 m2/g), and decreased pore volume (0.68 to 0.03 cm3/g), indicating successful framework constriction without collapse. Molecular simulations supported experimental trends, showing reductions in pore volume, crystallinity, and surface area with increasing bIm content. These ZIF-7-8 crystals were embedded in polysulfone to fabricate mixed matrix membranes, exhibiting improved H2/CO2 separation with a selectivity of 4.40 and H2 permeability of 9.42 Barrer, outperforming ZIF-8/PSF (3.07) and neat PSF (1.78). Simulated gas transport revealed a decline in CO₂ diffusivity (9.5 × 10−9 to 8.2 × 10− 10 m2/s) and increased H2 diffusivity (1.14 × 10− 8 to 1.68 × 10− 8 m2/s), boosting diffusion selectivity from 9.8 to 20.4. This work highlights the potential of the DLA method for designing tunable MOF materials tailored for gas separation applications.